2020
DOI: 10.1038/s41551-019-0510-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid optofluidic detection of biomarkers for traumatic brain injury via surface-enhanced Raman spectroscopy

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 95 publications
0
87
0
Order By: Relevance
“…Numerical modeling was carried out using a finite element solver COMSOL v4.3. The enhancement factor calculation is reproduced from ref ( 42 ). In brief, SERS enhancement factor was calculated by comparing the intensities of the unenhanced Raman scattering peak ( I Raman ) at 1 070 cm –1 of pure BT obtained by focusing the laser into a quartz cell and the corresponding SERS signals ( I SERS ) obtained from the SERS substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Numerical modeling was carried out using a finite element solver COMSOL v4.3. The enhancement factor calculation is reproduced from ref ( 42 ). In brief, SERS enhancement factor was calculated by comparing the intensities of the unenhanced Raman scattering peak ( I Raman ) at 1 070 cm –1 of pure BT obtained by focusing the laser into a quartz cell and the corresponding SERS signals ( I SERS ) obtained from the SERS substrates.…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 ] Until now, the diagnosis and prognosis of TBI have been heavily reliant on commonly used neuroimaging systems such as magnetic resonance imaging and computed tomography, which are the “gold standard” for evaluating TBI severity in acute care practices. [ 3 ] However, these neurological imaging systems are resource‐intensive and often unavailable for critically injured patients under austere conditions, which is especially relevant in battlefield environments. With the rapid development of nanotechnology, there has been growing interest in the use of promising nanoprobe‐based approaches for high‐sensitivity disease diagnosis, severity evaluation, and therapeutic assessment, especially for TBI detection in the field.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology, there has been growing interest in the use of promising nanoprobe‐based approaches for high‐sensitivity disease diagnosis, severity evaluation, and therapeutic assessment, especially for TBI detection in the field. [ 3,4 ] Among the numerous imaging strategies, dark‐field imaging is an approach with high signal‐to‐noise ratio that is not affected by autofluorescence and prevents photodamage and photobleaching. [ 5 ] Furthermore, due to strong local surface plasmon resonance (LSPR) signals, antibody functionalized plasmonic nanoparticles, especially gold nanoparticles (AuNPs), can be developed as dark‐field imaging contrast‐generating probes, which are applicable for dynamic single‐particle quantification at a single‐cell level.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral position of SPRs can be tuned by the geometry, composition, size, and shape of nanoparticles 31,32 . SERS is widely used in biochemistry, pharmacology, and biomedical sciences 33,34 . We showed that mitochondria suspension placed on Ag nanostructured surface gives an intensive SERS spectrum corresponding to SERS spectrum of cytC heme 26 .…”
Section: Introductionmentioning
confidence: 99%